The Impact of Mindfulness-Based Initiatives on Employee Engagement: An Integrative Review - Desai, Foram (Auckland University of Technology, 2024)
This review synthesises and evaluates two decades of empirical research on mindfulness-based interventions (MBI) and general mindfulness in the workplace environment to reveal key insights into its relationship with employee engagement. To offer an understanding of MBIs and how they impact employee engagement to inform research and practice, 25 peer-reviewed empirical journal articles are reviewed. The results are organised into an integrated framework showing direct relationships between MBI, general mindfulness, and employee engagement, and indirect relationships through mediator variables. The findings reveal that existing research on MBI and mindfulness is disproportionally focused on employee well-being-related outcomes and performance-related outcomes other than employee engagement – despite evidence that MBI and mindfulness could crucially impact how engaged employees are with their work tasks. Overall, MBI and mindfulness have direct and indirect relationships with employee engagement. Although developed for the workplace context, the proposed integrated framework can be applied to a range of industries and professions.